A structural analysis of DNA binding by hSSB1 (NABP2/OBFC2B) in solution - O'BYRNE, KEN (My University, 2016)
Single-stranded DNA binding proteins (SSBs) play an important role in DNA processing events such as replication, recombination and re- pair. Human single-stranded DNA binding pro- tein 1 (hSSB1 / NABP2 / OBFC2B) contains a single oligosaccharide / oligonucleotide binding (OB) do- main followed by a charged C-terminus and is struc- turally homologous to the SSB from the hyperther- mophilic crenarchaeote Sulfolobus solfataricus .Re- cent work has revealed that hSSB1 is critical to ho- mologous recombination and numerous other im- portant biological processes such as the regulation of telomeres, the maintenance of DNA replication forks and oxidative damage repair. Since the ability of hSSB1 to directly interact with single-stranded DNA (ssDNA) is paramount for all of these processes, un- derstanding the molecular details of ssDNA recogni- tion is essential. In this study, we have used solution- state nuclear magnetic resonance in combination with biophysical and functional experiments to struc- turally analyse ssDNA binding by hSSB1. We reveal that ssDNA recognition in solution is modulated by base-stacking of four key aromatic residues within the OB domain. This DNA binding mode differs signif- icantly from the recently determined crystal structure of the SOSS1 complex containing hSSB1 and ssDNA. Our findings elucidate the detailed molecular mecha- nism in solution of ssDNA binding by hSSB1, a major player in the maintenance of genomic stability.
Keywords: Single-stranded DNA binding proteins (SSBs); Single-stranded DNA binding proteins (SSBs)